تخفيض تأثير ظاهرة الانتقال المتكرر والمتذبذب في شبكات LTE النقالة باستخدام برنامج TRIAS - هيثم الرضوان; عدنان معترماوي; كنان غانم (Tishreen University, 2019)
Improving system performance in terms of data rate, mobility and cost is the scope of Long Term Evolution (LTE) system. In LTE networks the handover (HO) decision is performed by the evolved base station (eNB). The ping-pong movement in LTE is one of the most crucial problems which reduce the quality of the connection and degrade the performance of the handover. In this paper, the impact of ping-pong handover on inter eNB handover is investigated. The main object of the present work is to provide a method for reducing the number of ping-pong handover in the intra E-UTRA networks. A novel handover algorithm, based on keeping the old path between the source eNB and SGW/MME during the ping-pong movement and delaying the completion handover part, is presented. The ping-pong detecting algorithm for intra E-UTRA can be a tool to reduce the number of ping-pong handovers and control the demand of the network resources. Different values for the timer have been implemented and the probability of dropped calls and the ping-pong HO rates have been shown. Optimal timer value should be chosen carefully to reduce the probability of ping-pong HO and at the same time keep the dropped calls rate at lowest levels. Low and medium fixed user speed were implemented in this simulation mainly they are 25 km an hour and 70 km an hour. The analysis of the proposed algorithm showed that the rate of ping-pong handover can be reduced and, consequently, the handover quality indicator increased. Simulated results using TRIAS tools supported with NS2 simulator show that there is a significant reduction in the probability of the ping-pong handover when applied our proposed algorithm. يتركز مجال الاهتمام لنظام LTE بشكل أساسي على معدل إرسال البيانات، وقابلية الحركة والانتقال، وتكلفة النظام. إن أمر التسلّم والتسليم (Handover decision) بين الخلايا المتجاورة في نظام LTE يتم إقراره في المحطة القاعدية المطورة (evolved Base station). من أهم المشكلات التي تخفض جودة الاتصال، وتضعف الأداء في أثناء عملية الاستلام و التسليم بين المحطتين المتجاورتين هي حركة الانتقال المتكررة المتذبذبة (ping-pong HO) لمسار الاتصال بين المحطة المصدر والمحطة الهدف, ويستعرض هذا البحث تأثير هذه الظاهرة في أثناء عملية الاستلام و التسليم في شبكة LTE النقالة، ويهدف إلى تقديم طريقة جديدة لتخفيض عدد مرات التأرجح لمسار الاتصال بين الخلية المصدر و الخلية الهدف في شبكات LTE. تم اقتراح خوارزمية جديدة للاستلام والتسليم بين المحطات تعتمد على الاحتفاظ بالمسار القديم للإشارة (بين المحطة المصدر والبوابة المخدمة) في أثناء فترة التأرجح، وتأخير عملية إكمال الجزء النهائي من عملية الاستلام والتسليم. يمكن أن تشكل الخوارزمية المقترحة حلاً لتخفيض عدد مرات التأرجح غير المرغوبة، والتحكم بإدارة الحركة للنظام، والحفاظ على مصادر الشبكة اللاسلكية.في التحليل المقدم للخوارزمية تم اعتماد قيم مختلفة للعداد المستخدم في الخوارزمية, وتم عرض معدلات المكالمات المنقطعة، واحتمال حدوث الانتقال المتكرر المتذبذب. إن تحديد القيم المثلى لعداد التأخير يتطلب عناية ودقة ليضمن تخفيض معدل احتمال حدوث الانتقال المتكرر المتذبذب، وليضمن في الوقت نفسه بقاء معدلات المكالمات المنقطعة في أدنى المستويات. كذلك تم اعتماد سرعتين ثابتتين للمشترك في مجال السرعة المنخفضة والمتوسطة؛ وهما بشكل رئيس 25 و70 كم/سا. أثبتت نتائج هذه الدراسة أنه بالإمكان تخفيض معدل الانتقال المتكرر والمتذبذب بين الخلايا المتجاورة، وبالتالي تحسين قيمة مؤشر النوعية لعملية الاستلام والتسليم. وأظهرت نتائج النمذجة المعتمدة على برنامج TRIAS حدوث انخفاض ملحوظ في احتمال حدوث الانتقال المتكرر المتذبذب في أثناء عملية التسليم والاستلام عند تطبيقنا للخوارزمية المقترحة.